(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2015)
The essence of category «standard of living» is defined in the article. Its quantitative and qualitative parameters, factors of influence are determined. The indicators to measure the level of social protection of the population as a systematic concept to characterize the living standards are systematized. The role of distributive relations in the socioeconomic development is observed. The positive and negative aspects of changes in society during market transformations, dynamics and structure of income of the Ukrainian population are analyzed. It is shown that despite the importance of all forms of social protection of citizens, the fundamental principles the welfare of their own income received in the work place in the form of wages. Its size plays a decisive role in shaping the capabilities to meet the need sand ensure a decent standard of living. The necessity of a deep correction of market reform of the economy, its social orientation based on the change of meaning and mechanisms of social and economic policy is rationalized.